Submicronic Laue diffraction to determine in‐depth strain in very closely matched complex HgCdTe/CdZnTe heterostructures with a 10−5 resolution. (13th November 2020) - Biquard, X.; Ballet, P.; Tuaz, A.; Jouneau, P. H.; Rieutord, F.
Abstract : The strain profile inside very low lattice‐mismatched HgCdTe/CdZnTe multilayer stacks used in complex dual‐band IR detector was successfully measured with the required strain resolution of 10 −5 . Combined with chemical‐sensitive techniques, this approach allows correlation of lattice‐mismatch, interface compositional gradient and strain while isolating specific layer contributions. Abstract : Cross‐sectional submicronic Laue diffraction has been successfully applied to HgCdTe/CdZnTe heterostructures to provide accurate strain profiles from substrate to surface. Combined with chemical‐sensitive techniques, this approach allows correlation of lattice‐mismatch, interface compositional gradient and strain while isolating specific layer contributions which would otherwise be averaged using conventional X‐ray diffraction. The submicronic spatial resolution allowed by the synchrotron white beam size is particularly suited to complex infrared detector designed structures such as dual‐color detectors. The extreme strain resolution of 10 −5 required for the very low lattice‐mismatch system HgCdTe/CdZnTe is demonstrated.